Development of a Lateral Flow Kit for Detection of IgG and IgM Antibodies Against Rift Valley Fever Virus in Sheep - Sayed, Rafik H; Abousenna, Mohamed S; Mohamoud, Darwish; Saad, Mohamed A (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Rift Valley Fever (RVF) is a viral zoonosis that primarily affects animals but also has the capacity to infect humans. The disease also results in significant economic losses due to death and abortion among RVF-infected livestock. A lateral flow device (LFD) was developed for the rapid detection of IgG and IgM anti-RVF antibodies in infected and vaccinated ovine sera. The conjugated RVF antigen with nano gold was used as a detector antigen and was laid on a conjugated pad. The staphylococcal protein A was used as the capture complex (antibodies IgG-antigen conjugated with nanogold) at the first test line of device and anti-IgM antibodies were used as the capture complex (antibodies IgM-antigen conjugated with nanogold) at the second test line of device. When compared with RVF specific ELISA, The sensitivity, specificity, and accuracy of developed LFD for detection of IgG were found to be 88.2, 96.9 and 94.0%, respectively, while the same for detection of IgM was found to be 100, 96, and 96%, respectively.